Little Sinners, and Other Stories - Brown, Karen (Prairie schooner book prize in fiction., 2012)
Winner of the Prairie Schooner Book Prize in Fiction, Karen Brown's Little Sinners, and Other Stories features a sad, strange mosaic of women and men grappling with the loss and pain of everyday existence, people inhabiting a suburban landscape haunted by ghosts: a mother who leaps from a ridge, a mistress found at the bottom of the Connecticut River, a father who dresses in a pale blue-custom suit--and disappears. The dead leave behind postcards, houses, bottles of sherry, bones.